Programa de ações de arteterapia para pessoas idosas - Freitas, Ana Zuli Vidal Moreira de (2019)
Introduction: nowadays strategies are encouraged to strengthen the social and economic insertion of the elderly in society with the use of art therapy as a therapeutic activity aimed at the elderly population, it is not limited to registering behaviors or symptoms typical of old age, on the contrary, it rescues proposals, studies and ideas to reach means in defense of healthy aging. Objectives: to apprehend the scientific evidence on art therapy for the elderly; to know the opinion of elderly people about the practice of art therapy and to propose a program of art therapy actions for elderly people. Method: this is a methodological study developed in three stages: the first comprised a systematic review; the second held a semi-structured interview with 13 elderly women attended at a Primary Care service and the third elaborated the product. Results and Discussion: the results learned from the systematic review from searches in the databases: Medline, Scopus, Web of Science, Cochrane and Lilacs, in a comprehensive and unrestricted manner to the year or language of publication. Five articles were identified for the final sample, out of a total of 1,297 initial articles. From the analyzed articles, all answered the question that art therapy brings benefits and improves the quality of life of the elderly person by working on aspects of socialization to strengthen self-image, providing new manual skills. The collected data were submitted to a content analysis technique pointing out the classes or categories: 1: Descriptions of the therapy as learning, contemplating the units of analysis or texts in which the elderly describe the therapy as forms of learning, corresponding to 28% of the statements; 2: Descriptions of the psychological effects of therapy, formed by the units of analysis or texts in which elderly women talk about the impact of therapy on physical and metal health, with 34% of the statements and 3: Descriptions of therapy on physical health and the mental, formed by 38% of the answers. Conclusion: it was found that art therapy as a strategy to overcome internal and external difficulties stimulates the overcoming of your personal limits, either by practicing what you already know or by the desire to learn new arts ranging from social search to communication via social network as a way to reframe life. The program proposal for the elderly is an important activity to be used in different services. Thus, it is expected that this program will contribute, in particular to stimulate participants, to attract them to social groups, after retirement, for a better quality of life for the elderly.